Interpreting Waqf Accountability from The Perspective of Indonesian Waqf Managers - Lating, Ade Irma Suryani; Aripratiwi, Ratna Anggraini; Muflihin, Mohammad Dliyaul; Susanto, Febry Fabian; Ilmi, Muhammad Auliya' Nurul (AKTSAR: Jurnal Akuntansi Syariah, 2025)
This transcendental phenomenological study aims to interpret the meaning of waqf accounting through the lived experiences of Indonesian waqf managers (nazhir). Data were collected through in-depth interviews and active observation over approximately two months with three nazhirs representing different institutional settings (a waqf foundation, a waqf institution, and a mosque). The analysis followed phenomenological steps of epoche (bracketing), data horizontalization, clustering of meanings, and the synthesis of an “essence of meaning.” The findings indicate that nazhirs primarily understand waqf accounting as a compulsory recording practice that ensures waqf transactions are properly documented, accountable, and communicable to the public. However, the operational forms vary, ranging from simple manual cashbook records to integrated website-based systems. At the essential level, waqf accounting is perceived as dual accountability: accountability to God (habluminallah) and accountability to people/the public (habluminannas), reflected in commitments to honest, fair, and transparent reporting and to safeguarding the trust (amanah) in line with the waqif’s intention. These results highlight accountability and transparency as foundational mechanisms for strengthening public trust and preventing conflict in waqf management. Practically, the study suggests strengthening reporting capabilities, standardizing procedures, leveraging digital technology, and sustaining public outreach through collaborative efforts among government, waqf institutions, and communities to foster a healthier waqf ecosystem.